Adobe Photoshop CS3 top 100 simplified tips & tricks - Kent, Lynette (Visual read less, learn more, 2007)
A guide to Adobe Photoshop CS3 provides illustrated, step-by-step instructions for such tasks as working with layers, cropping and resizing photographs, retouching portraits, enhancing colors and tones, and designing with text effects. This book provides adventurous Photoshop users with a visual reference on how to use the bells and whistles found in the latest version of Photoshop. Broken out in 10 chapters, with 10 tasks per chapter, it covers 100 cool and useful tips and tricks that can be performed in the newest release of Photoshop. Full-color screen shots and numbered, step-by-step instructions show you how to take their Photoshop skills to new heights.